CORRECTION OF SECRETORY ACTIVITY OF THE SALIVARY GLANDS AND QUALITATIVE PROPERTIES OF ORAL FLUID IN CHILDREN WITH MALIGNANT TUMORS OF THE ABDOMINAL CAVITY, RECEIVING CYTOTOXIC DRUGS - Tkachenko, P.I.; Попело, Ю.В. (World of Medicine and Biology, 2015)
The indexes obtained in the dynamics of observation and the nature of changes witnessed a tangible reduction of secretory activity of the salivary glands and marked changes in pH, optical density, viscosity and activity of alpha-amylase of oral fluid during treatment with chemotherapy drugs. Meanwhile, under the conditions of the additional introduction of the gel «Zoleh» in the form of applications to the composition of the measures allowed to carried out the correction of violations of most indexes which were studied.
Keywords: children; malignant tumors; oral liquid; correction